Ultrassom no tratamento pós-colheita de uvas cultivar Isabel e Cabernet Sauvignon e sua influência na composição dos sucos - Comarella, Carine Glaucia (2012)
Phenolic compounds in plants have attracted considerable attention during the last decade due to their contribution to human health in reduce the risk of chronic diseases. The grape is one of the largest sources of these substances and like other plants, the synthesis of these compounds is usually associated with defense responses against stress factors, also called elicitors. More recently, ultrasound has been studied as possible abiotic elicitors of secondary metabolites due to mechanical stress and microstreaming induced by acoustic cavitation. Thus, this work aimed evaluate the application of different power densities (53 and 113 W cm-2) and exposure times (1, 5 and 10 minutes) to ultrasound in Isabel and Cabernet Sauvignon grapes about the effects on total polyphenols of juices made from this two cultivars. The samples were also subjected to the determination of total anthocyanins, tannins, total soluble solids, total acidity, pH and sensory evaluation. The Isabel cultivar showed more significant results in response to ultrasound, an increase of up to 83% in the levels of total polyphenols of juice, as well as significant increase in the content of total anthocyanins and tannins. These results were also accompanied by an increase in total soluble solids and total acidity of the juices. The application of ultrasound emphasized color, odor and taste of the Isabel grape juice, and the sonicated treatments were preferred by tasters. About Cabernet Sauvignon cultivar, it only showed a little variation in the most parameters. Power density and exposure time to ultrasound influenced the most of parameters evaluated in juices regarding to degree of response to sonication. Treatment with 5 and 10 min of exposure to ultrasound and power density of 113 W cm-2, is the combination that proved more effective for the elicitation of phenolic compounds by activation of plant secondary metabolism, improving the quality of the Isabel grape juice.